Use of the Cognitive Performance Test for Identifying Deficits in Hospitalized Older Adults. (14th May 2012) - Douglas, Alison; Letts, Lori; Eva, Kevin; Richardson, Julie
Abstract : Objectives . The Cognitive Performance Test (CPT) is a functional assessment for persons with dementia. The study purpose was to evaluate the reliability, discriminant, and concurrent validity of the CPT. Method . The CPT was tested against other measures of cognition (Standardized Mini Mental Status Exam (SMMSE) and Assessment of Motor and Process Skills-Process scale (AMPS-Process)). Participants were persons 65 years and older admitted to a geriatric rehabilitation unit (n = 47 ). Results . The CPT correlated moderately with measures of cognition (SMMSE r = 0.47, AMPS-Process r = 0.53, P < 0.01 ), and ADL burden of care (FIM r = 0.32, P < 0.05 ). Scores were not affected by age, sex, years of education, motor skills, or comorbidities. The CPT differentiated between impaired and unimpaired individuals differently from other measures. Conclusion . While CPT appears related to other measures of cognition, test interpretation requires noting the variability between CPT scores and those measures.